Pancasila Sebagai Strategi Ketahanan Bangsa di Era Disinformasi Digital - Nabila Azzahra; Dimas Ragil Sudiro Putro; Vito Arviansyah; Herli Antoni (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
In the era of digitalization, strengthening national identity is important, with the concept of National Defense as the main strategy. Defending the Nation emphasizes the obligation of every citizen to maintain the country's defense and security, especially amidst the threat of digitalization which can change cultural values and national identity. This research aims to examine the role of the concept of National Defense in strengthening national identity and increasing public awareness of the importance of defending the country. By maintaining the principles of Bhinneka Tunggal Ika and Pancasila, defending the country becomes a means of protecting Indonesia's unity, culture and sovereignty in the digital era.